1997
DOI: 10.1055/s-0038-1657709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gemfibrozil and Ciprofibrate on Plasma Levels of Tissue-type Plasminogen Activator, Plasminogen Activator Inhibitor-1 and Fibrinogen in Hyperlipidaemic Patients

Abstract: SummaryEvaluation of fibrate treatment in humans has focused primarily on its anti-lipidaemic effects. A potentially favourable haemostasis-modulating activity of fibrates has also been recognized but the data are not consistent. We sought to learn more about this variability by examining the effects of gemfibrozil and ciprofibrate on plasma levels of tissue-type plasminogen activator (t-PA), plasminogen activator inhibitor-1 (PAI-1) and fibrinogen in primary hyperlipidaemic patients after six and twelve weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
3
23
1
Order By: Relevance
“…4,6 However, clinical trials have demonstrated that fibrates producing a comparable triglyceride lowering have widely different effects on plasma PAI-1 activity. [7][8][9][10][11] This finding in vivo along with previous cell biological studies 12,13 and the present in vitro data from ECs strongly indicate that any fibrate effects on plasma PAI-1 activity in humans are at least partly a result of direct effects of the drug on PAI-1 synthesis in liver cells and/or ECs. The question then arises as to whether the diverse fibrate effects on PAI-1 expression in ECs observed in the present study could explain some of the discrepancies between the previous clinical trials.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…4,6 However, clinical trials have demonstrated that fibrates producing a comparable triglyceride lowering have widely different effects on plasma PAI-1 activity. [7][8][9][10][11] This finding in vivo along with previous cell biological studies 12,13 and the present in vitro data from ECs strongly indicate that any fibrate effects on plasma PAI-1 activity in humans are at least partly a result of direct effects of the drug on PAI-1 synthesis in liver cells and/or ECs. The question then arises as to whether the diverse fibrate effects on PAI-1 expression in ECs observed in the present study could explain some of the discrepancies between the previous clinical trials.…”
Section: Discussionsupporting
confidence: 79%
“…However, the results with respect to lowering of plasma PAI-1 activity have been discrepant: an overall significant effect, 7 an effect detectable on subgroup analysis only, 8,9 or no effect. 10,11 In comparison, studies of the effect of fibrates on PAI-1 synthesis in liver cells in culture have been more conclusive. Gemfibrozil suppresses PAI-1 synthesis in HepG2 cells, 12 and a range of fibrate compounds have been demonstrated to suppress PAI-1 synthesis in cultured cynomolgus monkey hepatocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This may not be surprising given that treatment with at least one of the agents studied, gemfibrozil, has previously been shown not to affect fibrinogen levels. 23 In summary, these data support the notion that fibrinogen is an independent risk factor for both all-cause mortality and CV death. This is also, to our knowledge, the first demonstration that elevated baseline fibrinogen predicts angiographic progression of existing CHD.…”
Section: Discussionsupporting
confidence: 73%